Desegregation, Accountability, and Equality: North Carolina and the Nation, 1971-2002 - Scott Baker; Anthony Myers; Brittany Vasquez (Arizona State University, 2014)
Using North Carolina as a lens to illuminate broader national developments, this paper examines how and why educational policy in the United States turned away from a civil rights agenda of opportunity and embraced test-based accountability as a way of promoting racial equality. We show that comprehensive desegregation, enforcement of the Civil Rights Act of 1964, and Great Society Programs expanded educational opportunities for African Americans, fueled significant increases in black educational achievement and attainment, and brought African Americans closer to equality with whites by the 1980s. We situate the turn to accountability in a political context shaped by an increasingly conservative political environment, and examine three overlapping waves of test- based accountability that began in North Carolina in the late 1970s and spread throughout the region and the nation in the decades that followed: the minimum competency movement of the late 1970s and early 1980s, the standards based reforms of the 1980s, and the more comprehensive and coercive forms of high stakes testing in the 1990s. We argue that the southern political leaders who shaped U.S. educational policy turned to test-based accountability as a politically expedient alternative to the task of equalizing educational opportunities for African Americans. Civil rights organizations endorsed test-based accountability, but we find little evidence that test-based approaches improved African American educational outcomes. Opportunity policies, we conclude, did more to promote racial equality in educational achievement and attainment than test-based accountability.